2023
DOI: 10.3349/ymj.2022.0422
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Focused Ultrasound and Photodynamic Treatment for Malignant Brain Tumors Using C6 Glioma Rat Model

Abstract: Purpose Glioblastoma (GBM) is an intractable disease for which various treatments have been attempted, but with little effect. This study aimed to measure the effect of photodynamic therapy (PDT) and sonodynamic therapy (SDT), which are currently being used to treat brain tumors, as well as sono-photodynamic therapy (SPDT), which is the combination of these two. Materials and Methods Four groups of Sprague-Dawley rats were injected with C6 glioma cells in a cortical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recent advances in PDT-GB research are as follows: (1) coupled NIR and photo immunotherapy (NIR-PIT), where a photosensitizer is conjugated to a highly specific monoclonal antibody [ 1043 , 1044 , 1045 ]; (2) NP-based PDT to augment systemic therapies and avoid skin photosensitization [ 1046 , 1047 ]; (3) NP-based PDT linked to miRNA or other chemotherapeutic agents [ 1048 ]; (4) strategies to increase PDT efficacy in hypoxic TME conditions [ 1049 , 1050 , 1051 , 1052 ]. Although some studies have demonstrated the enhanced penetration of light by simultaneous application of ultrasounds [ 1053 ], combined effects of PDT and SDT did not show any benefit in glioma rat models [ 1054 ].…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%
“…Recent advances in PDT-GB research are as follows: (1) coupled NIR and photo immunotherapy (NIR-PIT), where a photosensitizer is conjugated to a highly specific monoclonal antibody [ 1043 , 1044 , 1045 ]; (2) NP-based PDT to augment systemic therapies and avoid skin photosensitization [ 1046 , 1047 ]; (3) NP-based PDT linked to miRNA or other chemotherapeutic agents [ 1048 ]; (4) strategies to increase PDT efficacy in hypoxic TME conditions [ 1049 , 1050 , 1051 , 1052 ]. Although some studies have demonstrated the enhanced penetration of light by simultaneous application of ultrasounds [ 1053 ], combined effects of PDT and SDT did not show any benefit in glioma rat models [ 1054 ].…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%